The Influence of Workload on Work Motivation of Health Workers at the Sukatani Community Health Center in Purwakarta - Marliana, Rina; Djaali, Nur Asniati; Endarti, Ajeng Tias (LPPM Universitas Mohammad Husni Thamrin, 2025)
Health workers who are less motivated to work will show less than optimal performance, characterized by higher levels of fatigue, decreased work discipline, and decreased concern for service quality. Often the lack of motivation is caused by things such as lack of opportunities for career development, inadequate compensation, excessive workload, and lack of appreciation for performance. To determine the effect of workload on the work motivation of health workers at the Sukatani Health Center in Purwakarta. This study uses a quantitative research method with a cross-sectional approach. The sampling technique uses a total sampling method of 60 health workers at the Sukatani Health Center in Purwakarta. Bivariate analysis uses the chi-square test and multivariate analysis uses multiple logistic regression. Based on the Chi-square test, the P value is 0.000 <0.05, which indicates that there is a significant influence between workload on the motivation of health workers at the Sukatani Health Center with an Odd Ratio (OR) value of 13. The results of the multiple logistic regression test obtained the largest result of 63.865 which indicates that the variable number of positions as the most dominant confounder factor influences workload on work motivation. Health center management should develop policy plans that can reduce workload and increase employee motivation by managing time wisely to help reduce stress, conducting open discussions in finding solutions together with task division and target adjustments, delegating tasks and integrating activities to increase efficiency, ensuring adequate rest to avoid physical and mental fatigue, optimizing the use of existing systems to reduce manual workload, providing regular training on occupational safety (K3).